Insights into ancient ceramic technology: a comprehensive analysis of mineralogy, chemistry and firing conditions - Mammadov, S.; Ahadova, A. (Recent Research in Science and Technology, 2024)
The intensive integration of Azerbaijan into the global economy, mainly through international gas and oil pipeline construction, has led to significant archaeological research in the past two decades. The construction of the Baku-Tbilisi-Ceyhan oil pipeline (BTC) and the Southern Caucasus Pipeline gas pipeline (SCP) prompted a four-year archaeological fieldwork program, followed by a six-year post-excavation program. The current work applied an interdisciplinary approach using various instrumental methods for studying ancient artifacts found during those projects. The thermogravimetric method and differential thermal analysis were employed to obtain insights into the production technology of the ancient pottery and information about the mineralogy of the ceramic sherds. The complex processes involved in firing the ceramic paste have been studied extensively, and patterns in mass loss ratios during different temperature ranges have been established. In total, 15 samples were investigated, and the thermogravimetric analysis of ceramic shards revealed that the firing temperature of the samples was in the range of 700 °C. XRD analysis confirmed the presence of quartz, feldspar, and clay minerals in the ceramic samples. The presence of calcite and other specific minerals is subject to the origin of the ceramic materials. The results obtained from this multidisciplinary approach provide insights into the firing technology and the origin of the ceramic samples.